Effects of Sodium Nitrite and Tocopherol Incorporated Poly(Lactic Acid) Biodegradable Films on Dark-Cutting Beef Color - Anibal Bher; Gretchen Mafi; Mansour Alnajrani; Morgan L. Denzer; Morgan Pfeiffer; Rafael Auras; Ranjith Ramanathan; Timothy Bowser; Trinity J Smith; Wesley Osburn (Meat and Muscle Biology, 2024)
This study aimed to develop poly(lactic acid) (PLA) biodegradable film containing sodium nitrite and α-tocopherol, and to examine its effect on dark-cutting beef color attributes. Using a twin-screw extruder, PLA pellets were manufactured as a low-concentration (LC) PLA pellet containing 0.12% sodium nitrite and 0.5% α-tocopherol or a high-concentration (HC) PLA pellet containing 0.6% sodium nitrite and 2.5% α-tocopherol. Extruded PLA pellets were oven-dried before being compressed and molded into film sheets using a hot press. In this study, 7 normal-pH and 7 dark-cutting strip loins were selected from a commercial processor. Loins were sliced into 2.54-cm thick steaks and randomly assigned to the respective loin-type treatments. The packaging treatments include normal-pH polyvinyl chloride (PVC), dark-cutting PVC, dark-cutting vacuum, LC-PLA dark-cutting in vacuum, and HC-PLA dark-cutting in vacuum. Normal-pH steaks were packaged with PVC overwrap, while dark-cutting control steaks were packaged in PVC overwrap and vacuum-sealed. The respective PLA films (LC or HC) were placed directly on the surface of the dark-cutting steak surface before vacuum packaging, resulting in LC-PLA and HC-PLA treatments. All steaks were placed in a simulated retail dis-play maintained at 2±1°C for 6 d, during which their surface color was evaluated every 24 h using a HunterLab spectrophotometer and a trained panel (n=6). Half of the steaks were removed from display on d 5 and cooked to 71°C on a George Foreman grill to evaluate the cooked color. The remaining steaks were evaluated on d 6 for microbial growth and lipid oxidation. A significant increase (P<0.05) in surface redness value was observed for steaks packaged with LC-PLA and HC-PLA within the first 24 h of display. Moreover, HC-PLA steaks exhibited higher redness values (P<0.05) than LC-PLA, dark-cutting PVC, and dark-cutting vacuum-packaged steak treatments over the entire display period. Steaks packaged with HC-PLA demonstrated greater external cooked color redness (P<0.05) and greater internal cooked color redness (P<0.05) than normal-pH steaks in PVC overwrap and dark-cutting steaks in PVC overwrap and vacuum packaging. Notably, LC-PLA steaks presented similar external and internal cooked color redness (P>0.05) compared to dark-cutting steaks in control vacuum packages (without nitrite). There were no differences (P>0.05) in aerobic plate count and lipid oxidation between nitrite-embedded and control vacuum dark-cutting treatments. Results indicate that using lower concentrations of sodium nitrite (0.12%) andα-tocopherol (0.5%) in PLA films can help improve the surface color of raw dark-cutting steaks while minimizing unpleasant cooked color associated with nitrite-embedded film.